Challenges and Opportunities for High School History Teachers in Using TikTok and Other Social Media for Learning - Anggiani, Anggiani; Dewi, Oktavia; Simanjuntak, Cresensia Anggreni; Barus, Amarta Florida br; Sari, Ika Purnama (Universitas Syiah Kuala, 2025)
This study aims to examine the challenges and opportunities faced by high school history teachers in utilizing social media, especially TikTok, as a learning medium. With a descriptive qualitative approach, data was collected through in-depth interviews, content observations, documentation studies, and open questionnaires to teachers and students in the city of Medan and its surroundings. The results show that teachers face a number of challenges, including limited digital skills, limited time to create content, lack of institutional support, and obstacles to access to technology and the internet. However, behind these challenges, TikTok and other social media open up great opportunities in creating more interesting, visual, and contextual historical learning for the digital native generation. Teachers who are able to innovate in the use of social media have been proven to increase student engagement, build a living historical narrative, and create participatory and collaborative learning spaces. The strategies implemented include collaboration with students in content production, adaptation of popular trends, and the use of TikTok's interactive features. This study concludes that the success of the use of social media in history learning is determined by teachers' readiness in pedagogical and digital aspects, as well as support from the school environment and education policies. Therefore, strengthening digital literacy and policies that support social media-based learning innovations is needed to create relevant, creative, and meaningful historical education in the digital era.